Acute Acalculous Cholecystitis Associated with Hepatitis A Viral Infection: A Case Report - Ariobimo, Bonfilio Neltio; Nujum, Nurun; Saputro, Daniel Ponco Harto (Institute of Topical Disease Universitas Airlangga, 2023)
Most hepatitis A infections are acute, self-limiting, and asymptomatic. In rare instances, extra hepatic complication, such as acute cholecystitis, may emerge. Acute cholecystitis is inflammation of the gallbladder wall and is classified into calculus and acalculus. About 90–95% of cases are brought on by bile duct stones. Acute acalculous cholecystitis can be brought on by structural and functional abnormalities in the gallbladder brought on by viral hepatitis infection. Here we present a 20 years old female patient with acute acalculous cholecystitis associated with hepatitis A infection. Gallbladder distention, thickening of the gallbladder wall, absence of acoustic shadow or biliary sludge, perivesical liquid buildup, and absence of dilatation of the intra- and extrahepatic bile ducts are among the ultrasonographic criteria for diagnosing acute acalculous cholecystitis. The viral hepatitis serology revealed acute hepatitis A infection with positive anti-HAV IgM. Hepatitis A testing should be considered in patients suspected with acalculous cholecystitis of undefined etiology in markedly deranged liver function test adult patients.